InSAR time series analysis of seasonal surface displacement dynamics on the Tibetan Plateau - Reinosch, Eike; Buckel, Johannes; Dong, Jie; Gerke, Markus; Baade, Jussi; Riedel, Björn (The Cryosphere, 2020)
Climate change and the associated rise in air temperature have affected the Tibetan Plateau to a significantly stronger degree than the global average over the past decades. This has caused deglaciation, increased precipitation and permafrost degradation. The latter in particular is associated with increased slope instability and an increase in mass-wasting processes, which pose a danger to infrastructure in the vicinity. Interferometric synthetic aperture radar (InSAR) analysis is well suited to study the displacement patterns driven by permafrost processes, as they are on the order of millimeters to decimeters. The Nyainqêntanglha range on the Tibetan Plateau lacks high vegetation and features relatively thin snow cover in winter, allowing for continuous monitoring of those displacements throughout the year. The short revisit time of the Sentinel-1 constellation further reduces the risk of temporal decorrelation, making it possible to produce surface displacement models with good spatial coverage. We created three different surface displacement models to study heave and subsidence in the valleys, seasonally accelerated sliding and linear creep on the slopes. Flat regions at Nam Co are mostly stable on a multiannual scale but some experience subsidence. We observe a clear cycle of heave and subsidence in the valleys, where freezing of the active layer followed by subsequent thawing cause a vertical oscillation of the ground of up to a few centimeters, especially near streams and other water bodies. Most slopes of the area are unstable, with velocities of 8 to 17 mm yr−1. During the summer months surface displacement velocities more than double on most unstable slopes due to freeze–thaw processes driven by higher temperatures and increased precipitation. Specific landforms, most of which have been identified as rock glaciers, protalus ramparts or frozen moraines, reach velocities of up to 18 cm yr−1. Their movement shows little seasonal variation but a linear pattern indicating that their displacement is ...